Impact of social support, prosocial behaviour, basic psychological needs on life satisfacation and self-esteem as a mediator among Chinese university students in Shandong - Yuan, Yuan (Tanjong Malim, 2024)
Impact of social support, prosocial behaviour, basic psychological needs on life satisfacation and self-esteem as a mediator among Chinese university students in Shandong by Yuan, Yuan